Health-related quality of life and its associated factors among adult patients with type II diabetes attending Mizan Tepi University Teaching Hospital, Southwest Ethiopia - Tadesse Gebremedhin; Abdulhalik Workicho; Dessie Abebaw Angaw (BMJ Open Diabetes Research & Care)
Background Health-related quality of life (HRQOL) has become an important measure for evaluating patient treatment with non-curable chronic disease. The aim of the study was to assess HRQOL and its associated factors among patients with type II diabetes.Methods This is an institution-based, cross-sectional study conducted from March 13 to May 9, 2018. A total of 267 patients with type II diabetes who visited the clinic for follow-up for at least 3 months and who were 18 years or older were included in the study. The WHO Quality of Life-BREF was used to assess quality of life. Multivariable linear regression was employed to identify associated factors with HRQOL among patients with type II diabetes.Results The mean score for overall HRQOL was 51.50±15.78. The mean scores for physical health, psychological, environmental and social relationship domains were 49.10±18.14, 53.51±19.82, 49.72±16.09 and 53.68±17.50, respectively. Age, disease duration and fasting blood glucose level were inversely associated with all domains of HRQOL (p<0.001). Body mass index was inversely related with all domains of HRQOL except with the physical health domain.Conclusion The findings from this study indicated that all dimensions of HRQOL of patients with diabetes in this study setting were compromised. The study also identified important predictors such as age, duration of disease and level of fasting blood sugar. This entails the need to intervene in improving the HRQOL of patients with diabetes beyond the provision of standard treatments.